A study on quality of hard-core poor government housing programme (PPRT) / Noor Hazwani A.Rahman - A.Rahman, Noor Hazwani (2009)
In many construction industries now days including the housing industry, the occupant satisfaction is very famous concept. Because of that the government has introduced CIS 2 as the minimum standardization requirements for low cost housing to see the quality in the housing industry. The objective of this survey is to determine occupant's satisfaction toward the quality of houses indicating design requirement and construction material and workmanship in low cost houses in the Perak area. The data collected by three methods which are by literature review, questionnaire survey and observations on PPRT housing. The respondents for the surveys covered sixty (60) people from with three (3) of the residential housing (PPRT) in Perak rural area. Microsoft Excel was used for data analysis based on frequency and average index analysis. The analysis shows the result that the provision under Construction Industry Standard 2 was fully implemented in three (3) PPRT housing surveyed. However, there are common workmanship defect experienced by the low cost housing dwellers mostly majority related to the building construction. Generally, the occupants are not satisfied with the quality of PPRT houses in term of its design, infrastructure, facilities and construction material.